Smartphone Addiction, Children's Mental Health, and the Role of Parenting - Reza Fajar Amalia; Achir Yani Syuhaimie Hamid (Jurnal Ilmu Keperawatan Jiwa, 2020)
Increased smartphone utilization by children will increase the risk of  addiction which consequently affecting the  physical and mental health status of  children. This impact requires an appropriate prevention strategies and involves the family or parents as important social support system for child's development. This study aim to identify systematically the effects of smartphone addiction on children, addiction prevention strategies, and formulation of guideline for parents in assisting their children when using smartphones. This study using systematic review by searching articles in electronic database (SpringerLink, ClinicalKey, SAGE Publication, Annual Reviews). The keywords used are "smartphone addiction" AND "mental health" AND "children" OR "child". The result of 13 relevant arcticles analysis revealed that the most common effects of smartphone addiction on mental health of children were anxiety, depression and behavioral disorders. Anxiety, depression and behavioral disorders have a two-way relationship with smartphone addiction. Authoritative parenting style can reduce the risk of smartphone addiction. Smartphone addiction requires a comprehensive prevention and intervention strategy. In addition, authoritative parenting style make the child into a person who has a character that will later influence attitudes, ways of thinking to avoid addictive behavior.